Effects of Minority Stress, Group-Level Coping, and Social Support on Mental Health of German Gay Men - Sattler, Frank A.; Wagner, Ulrich; Christiansen, Hanna (PloS one, 2016)
According to epidemiological studies, gay men are at a higher risk of mental disorders than heterosexual men. In the current study, the minority stress theory was investigated in German gay men: 1) it was hypothesized that minority stressors would positively predict mental health problems and that 2) group-level coping and social support variables would moderate these predictions negatively. Data from 1,188 German self-identified gay men were collected online. The questionnaire included items about socio-demographics, minority stress (victimization, rejection sensitivity, and internalized homonegativity), group-level coping (disclosure of sexual orientation, homopositivity, gay affirmation, gay rights support, and gay rights activism), and social support (gay social support and non-gay social support). A moderated multiple regression was conducted. Minority stressors positively predicted mental health problems. Group-level coping did not interact with minority stressors, with the exception of disclosure and homopositivity interacting marginally with some minority stressors. Further, only two interactions were found for social support variables and minority stress, one of them marginal. Gay and non-gay social support inversely predicted mental health problems. In addition, disclosure and homopositivity marginally predicted mental health problems. The findings imply that the minority stress theory should be modified. Disclosure does not have a relevant effect on mental health, while social support variables directly influence mental health of gay men. Group-level coping does not interact with minority stressors relevantly, and only one relevant interaction between social support and minority stress was found. Further longitudinal or experimental replication is needed before transferring the results to mental health interventions and prevention strategies for gay men.